The aesthetic concept in contemporary Iraqi painting (Journal of the College of Basic Education, 2025)
Plastic arts in general and graphic arts in particular depend on their vocabulary and themes as the formation and construction of a new text based on different environmental and life texts, and taking them as new formulations that retain the metaphorical image and the intended meaning in the painting and the plastic achievement, as the idea interacts with the technique with colors to indicate a kind of sharing and interaction at levels where the topics (deletion, addition, composition) overlap between its vocabulary. Where the benefit here is at the philosophical and intellectual level, and the meaning to a new text is an artistic painting that serves the recipient by displaying those achievements and plastic paintings to become one of the most exciting arts left by the painter through letters and his own artistic discourse, and through that excitement the aesthetic discourse has become directly influential on the artistic, cultural and academic medium, and then directly enters into the development, development and formation of the personality of the painter and then its impact on the recipients. These aesthetic concepts with their artistic discourses have taken a kind of assimilation in the preparation of the idea of the plastic painting of the painter, and then create it figuratively to become clear and visible through its aesthetic discourse, which develops its connotations its artistic discourse, where the researcher advanced in this study to prepare a scientific methodology was the plastic artistic texts with aesthetic discourse in the art of contemporary Iraqi painting, and display the mechanisms of diagnosis in them, and then the measurements of the impact of the recipient, and therefore the researcher went to achieve intellectual attachments and vital deliberative communication that played With the system of formal text, and at artistic levels, whether it is color, kinetic or indicative of the lines, and its purpose is to impose the aesthetic influence on the recipient, thus becoming a deliberative communication system in formative, signal, kinetic and color units that produced plastic artistic texts in which the researcher relied in their construction on the experience of contemporary Iraqi painters from the period 1960-1980, and focused on the embodiment of all artistic, sensory and intellectual requirements that achieve pleasure, knowledge and philosophy, and bring about influence and change in the behavior of the recipient. The researcher goes through the painter's borrowing of elements, symbols and icons from previous texts and repositioning and formulating them in a new context in which he keeps pace with the artistic schools of modernity and beyond, where they lead to influence and change because they have carried different connotations and forms from each other.